THE KALELA DANCE; ASPECTS OF SOCIAL RELATIONSHIP AMONG AFRICANS IN NORTHERN RHODESIA, by J. Clyde Mitchell (The Rhodes-Livingstone Papers No. 27), Manchester University Press (preface (dated June, 1956) (International Library of African Music, 1957)
pages: 59
Keywords: African Music; Social Relationship; Northern Rhodesia; Zimbabwe